Outbreak of respiratory syncytial virus infection in Eastern India during COVID-19 pandemic: An observational study from a single pediatric intensive care unit - Bubai Mandal; Satyabrata Roychowdhoury; Pinki Barui; Mithun Chandra Konar; Subhajit Bhakta; Mousumi Nandi; Mohammad Asraf Uz Zaman; Mihir Sarkar; Manas Kumar Mahapatra (Wolters Kluwer Medknow Publications, 2022)
Background: After the peak of the second wave of COVID-19 pandemic, we faced a surge of respiratory syncytial virus (RSV) infection. This study was aimed to estimate the severity, clinical course, and outcome of RSV-infected children admitted in pediatric intensive care unit and to identify the predictors of development of acute respiratory distress syndrome (ARDS). Subjects and Methods: This retrospective study included children below 5 years with influenza-like illnesses (ILI) due to RSV infection. The clinical, laboratory, treatment, and outcome-related parameters were assessed and a compared between ARDS and non-ARDS group. Results: Out of 44 ILI patients, 36 had RSV infection. Most of them (88.9%) were infants. Twenty-four (66.7%) patients developed ARDS and 9 (25%) were ventilated. Infants below 6 months, low birth weight (LBW) babies, consolidations (≥3 zones), interstitial edema (≥3 zones) in lung ultrasound, high pediatric sequential organ failure assessment (pSOFA), and Pediatric Risk of Mortality III score were significantly associated with ARDS. Conclusions: RSV-infected children with young age (1-6 months), LBW, higher lung ultrasound, and pSOFA score should alert physicians for progression to ARDS.